Human centered design second international conference, HCD 2011,held as part of HCI International 2011, Orlando, FL, USA, July 9-14, 2011, proceedings - HCI 2011 (2011 Orlando, F.L.); Kurosu, Masaaki; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
This volume constitutes the refereed proceedings of the Second International Conference on Human Centered Design, HCD 2011, held as Part of HCI International 2011, in Orlando, FL, USA, in July 2011, jointly with 9 other thematically similar conferences. The 66 revised papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical parts on human centered design methods and tools, mobile and ubiquitous interaction, human centered design in health and rehabilitation, human centered design in work, business and education, and applications of human centered design.
Electronic reproduction.
Keywords: Human engineering -- Congresses; Human-computer interaction -- Congresses; User interfaces (Computer systems) -- Design -- Congresses; User-centered system design -- Congresses; Electronic books